Horrible harry and the dragon war eaudiobook - Kline, Suzy (Horrible Harry, 2005)
Suzy Kline is a favorite author of children's books. Her best-selling Horrible Harry books are wonderful stories that any school-aged child will enjoy. According to Kirkus Reviews, "Kline hits the nail on the head once again by telling a real classroom story." In Room 3B, longtime best friends Horrible Harry and Song Lee are fighting. Song Lee hasn't spoken a word to Harry ever since their teacher, Miss Mackle paired them to work together. Will they make-up in time to present their project?